The structures and regulatory roles of natural products in lipid metabolism: focus on medicinal and edible plants - Xinjian Zhang; Sheng Li; Bodou Zhang; Yu Zhang (Food Science and Human Wellness)
Lipids are essential for normal life activities and biological functions of the human body, and disorders of lipid metabolism produce a lipotoxic environment, endoplasmic reticulum (ER) stress, inflammation, and cell death, which can lead to a variety of diseases in the body. It has been found that lipid metabolism disorders are closely associated with brain injury disease, cancer, metabolic disease, cardiovascular disease (CVD), respiratory disease and infectious disease. In recent years, many medicinal and edible plants such as Pueraria lobata, Gardenia jasminoides, Curcuma longa, citrus fruits, peanuts, etc. have shown great potential in regulating lipid metabolism and some of the hidden active components showed innovative mechanisms. AMPK, PPARγ, SIRT1, Foxp3, NLRP3, and Keap1 are increasingly recognized as therapeutic targets in the field of regulating lipid metabolism. This study aims to provide a comprehensive review of natural lipid-regulating modulators in medicinal and edible plants and their mechanism of actions, which offer valuable references for the discovery of natural lipid metabolism modulators and a therapeutic strategy for treatment of lipid metabolism-related diseases.